Determinants of Profitability of Agricultural Sector in Vojvodina: The Role of Corporate Income Tax - Vržina, Stefan Ž.; Dimitrijević, Miloš S. (The European Journal of Applied Economics, 2020)
Due to considerable share in total employment and foreign trade exchange, agriculture represents important sector of the Serbian economy. Therefore, it is necessary to continuously analyze financial performance of agricultural companies and key determinants of financial performance. Objectives of the paper are to analyze corporate income tax burden of agricultural companies in Vojvodina and its impact on company profitability. Statistical tests showed that effective corporate income tax rates (ETRs) in agricultural companies are significantly lower than statutory corporate income tax rate. Furtherly, nearly 69% of observations have both current ETR and cash ETR of 0%, which indicate that agriculture is an industry with exceptionally low corporate income tax burden. Ordinary least squares regression showed that agricultural companies with lower ETRs are more profitable than companies with higher ETRs. Results of analysis are not sensitive to changes of corporate income tax burden and profitability proxies.
Keywords: profitability; corporate income tax; Vojvodina; agriculture